Detailed study of SNR G306.3-0.9 using XMM-Newton and Chandra observations - Combi, Jorge Ariel (2016)
Aims. We aim to study the spatial distribution of the physical and chemical properties of the X-ray emitting plasma of the supernovaremnant (SNR) G306.3−0.9 in detail to obtain constraints on its ionization stage, the progenitor supernova explosion, and the age ofthe remnant.Methods. We used combined data from XMM-Newton and Chandra observatories to study the X-ray morphology of G306.3−0.9 in detail. A spatially resolved spectral analysis was used to obtain physical and geometrical parameters of different regions of the remnant. Spitzer infrared observations, available in the archive, were also used to constrain the progenitor supernova and study the environment in which the remnant evolved.Results. The X-ray morphology of the remnant displays a non-uniform structure of semi-circular appearance, with a bright southwest region and very weak or almost negligible X-ray emission in its northern part. These results indicate that the remnant is propagating in a non-uniform environment as the shock fronts are encountering a high-density medium, where enhanced infrared emission is detected. The X-ray spectral analysis of the selected regions shows distinct emission-line features of several metal elements, confirming the thermal origin of the emission. The X-ray spectra are well represented by a combination of two absorbed thermal plasma models: one in equilibrium ionization (VAPEC) with a mean temperature of ∼0.19 keV, and another out of equilibrium ionization (VNEI) at a higher temperature of ∼1.1 or 1.6?1.9 keV. For regions located in the northeast, central, and southwest part of the SNR, wefound elevated abundances of Si, S, Ar, Ca, and Fe, typical of ejecta material. The outer regions located northwest and south show values of the abundances above solar but lower than to those found in the central regions. This suggests that the composition of the emitting outer parts of the SNR is a combination of ejecta and shocked material of the interstellar medium. The comparison between the S/Si, Ar/Si, and Ca/Si abundances ratios (1.75, 1.27, and 2.72 in the central region, respectively), favor a Type Ia progenitor for this remnant, a result that is also supported by an independent morphological analysis using the X-ray and 24 µm IR data.